The cyclicality of Irish fiscal policy ex-ante and ex-post: A cross-country examination - David Cronin; Kieran McQuinn (The Economic and Social Research Institute (ESRI), 2017)
The cyclicality of fiscal policy in Ireland in the budgetary plans put before parliament and ex-post is considered. Data in budgetary documents and particular econometric estimation procedures help address endogeneity issues and provide numerous variable-estimation procedure combinations for assessing cyclicality. Fiscal policy in Ireland is found to be procyclical on both ex-ante and ex-post bases. The evidence is mixed between policy being more pro-cyclical ex-post than was intended at Budget time and there being no difference. With the preventive arm of the Stability and Growth Pact now applying to Ireland, a continuation of procyclical fiscal policy would endanger its requirements being met.
Keywords: E62; H61; H68; 330; Cyclicality; Policy